Tailoring anaesthetic strategies for diabetes research: Acepromazine vs. medetomidine in Aachen minipigs - Soares, Sabrina; Wühl, Elisabeth; Schlund, Alexander; Schneider, Tobias; Sohns, Kyra; Rukwied, Roman; Schmelz, Martin; Kränzlin, Bettina (PLOS ONE, 2025)
Pre-established anaesthetic protocols in animal models might unexpectedly interfere with the main outcome of scientific projects and therefore they need to account for the specific research goals. We aimed to optimize the anaesthetic protocol and animal handling strategies in a diabetes-related-study exemplifying how the anaesthetic approach must be adjusted for individual research targets. Aachen minipigs were used as a model to test long-lasting skin glucose sensors for diabetic human patients. A total of 6 animals participated in two or three rounds of experiments. Each round lasted 2 months, with a maximum of 2 rounds per year. In each round, animals were anaesthetised 4 times: for glucose sensors insertion, twice for glucagon stress tests (GST), and a last time for removal of sensors. Acepromazine (ACE) was compared to medetomidine (MED) in association with butorphanol (BUT) and Ketamine (KET) and 4 parameters were analysed to define the optimum anaesthetic protocol including: sedation level, anaesthesia duration, effects on blood glucose and safety. ACE-BUT demonstrated a weaker sedative effect but reduced overall experimental time, minimized anaesthetic risk and minimally interfered with the glucose metabolism. The improvement obtained by animal conditioning and handling strategies applied in this study were not objectively estimated, although the aversion behavior was completely abolished. Based on the analysed parameters, the use of acepromazine is proposed to be superior when Aachen Minipigs are used specifically as a model for diabetes-related studies, albeit the recommendations for the anaesthesia of minipigs suggest otherwise.
Gesehen am 26.08.2025